2021
DOI: 10.22541/au.162810199.97977434/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Low value Injury Care in the Adult Orthopaedic Trauma Population: A Systematic Review

Abstract: Objectives. Fifteen potentially low value practices in adult orthopaedic trauma care were previously identified in a scoping review. The aim of this study was to synthesize the evidence on these practices. Methods. We searched four databases for systematic reviews, randomized controlled trials (RCTs), cohort studies and case series that assessed the effectiveness of selected practices. Methodological quality was evaluated using the Measurement Tool to Assess Systematic Reviews version 2 (AMSTAR-2) for systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…One study evaluated the evidence behind 15 potentially low-value practices, identified by 36 experts. 31 Evidence was evaluated using a checklist for quality, and outcomes included complications and change in management. Several trauma practices for which evidence was lacking were identified, such as routine initial imaging of ankle injuries, an orthosis for an A0-A3 thoracolumbar burst fracture in patients <60 years of age, casting or splinting for a fifth metacarpal neck fracture and for an MRI-negative scaphoid fracture, and routine follow-up imaging for distal radial and ankle fractures.…”
Section: Miscellaneous Topicsmentioning
confidence: 99%
“…One study evaluated the evidence behind 15 potentially low-value practices, identified by 36 experts. 31 Evidence was evaluated using a checklist for quality, and outcomes included complications and change in management. Several trauma practices for which evidence was lacking were identified, such as routine initial imaging of ankle injuries, an orthosis for an A0-A3 thoracolumbar burst fracture in patients <60 years of age, casting or splinting for a fifth metacarpal neck fracture and for an MRI-negative scaphoid fracture, and routine follow-up imaging for distal radial and ankle fractures.…”
Section: Miscellaneous Topicsmentioning
confidence: 99%